Transcriptome Profile Analysis on Ovarian Tissues of Autotetraploid Fish and Diploid Red Crucian Carp - Wang, Yude; Zhang, Minghe; Qin, Qinbo; Peng, Yajun; Huang, Xu; Wang, Chongqing; Cao, Liu; Li, Wuhui; Tao, Min; Zhang, Chun; Liu, Shaojun (Frontiers in Genetics, 2019)
Polyploidization can significantly alter the size of animal gametes. Autotetraploid fish (RRRR, 4nRR = 200) (4nRR) possessing four sets of chromosomes were derived from whole-genome duplication in red crucian carp (RR, 2n = 100) (RCC). The diploid eggs of the 4nRR fish were significantly larger than the eggs of RCC. To explore the differences between the ovaries of these two ploidies of fishes at the molecular level, we compared the ovary transcriptome profiles of 4nRR fish and RCC and identified differentially expressed genes (DEGs). A total of 19,015 unigenes were differentially expressed between 4nRR fish and RCC, including 12,591 upregulated and 6,424 downregulated unigenes in 4nRR fish. Functional analyses revealed that eight genes (CDKL1, AHCY, ARHGEF3, TGFβ, WNT11, CYP27A, GDF7, and CKB) were involved in the regulation of cell proliferation, cell division, gene transcription, ovary development and energy metabolism, suggesting that these eight genes were related to egg size in 4nRR fish and RCC. We validated the expression levels of these eight DEGs in 4nRR fish and RCC using quantitative PCR. The study results provided insights into the regulatory mechanisms underlying the differences in crucian carp egg sizes.